Immune-microbiota interactions in health and disease - Palm, Noah W. (Clin Immunol, 2015)
Recent studies have revealed that the intestinal microbiota plays an important role in host physiology and pathophysiology in health and disease. One of the major mechanisms by which the gut microbiota influences the host is through its interactions with and effects on the host immune system. In this review, we discuss the reciprocal interactions between the host immune system and the gut microbiota, with a particular focus on individual microbes that impact the host through dramatic and specific interactions with the adaptive immune system. We highlight the idea that the presence or absence of specific immunologically important members of the microbiota can determine disease susceptibility and propose that the identification and characterization of these bacteria in humans will eventually allow us to elucidate the role of microbiota composition in human disease.